Exploring Consumer Behavior in Coffee Shops: How Store Atmosphere and Sustainability Marketing Affect Purchase Intentions through Perceived Value - Dirgandana, Ghaqa; Tamara, Dewi (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Recent years, academic and practical attention toward store atmospherics has grown, driven by its consideraable impact on consumer behavior. Simultaneously, sustainability has emerged as a prominent topic across various industries, including the culinary sector. This study investigates how store atmosphere and sustainable marketing practices affect consumer purchase intention, emphasizing the mediating role of perceived value, specifically in the context of coffee shop consumption behavior in Indonesia. Data were collected via an online survey targeting frequent local coffee shop visitors, yielding 200 respondents through convenience sampling. The study utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique for analysis, with SmartPLS 3.0 software serving as the primary analytical tool. The dependent variable is purchase intention, while the independent variables comprise store atmosphere and sustainability marketing, with perceived value functioning as an intermediary factor in the model. The results indicate, first, that a significant and positive effect is exerted by store atmosphere on consumers’ purchase intention. Second, sustainability marketing does not demonstrate a direct and statiscally notable influence on consumers' buying decisions. Finally, Perceived value serves as a crucial intermediary in the linkage between store atmospherics, sustainability marketing, and purchase intention within Indonesian coffee shops.